Effect of Sarcopenia on Mortality and Spinal Cord Ischaemia After Complex Aortic Aneurysm Repair: Systematic Review and Meta-Analysis. (April 2023) - Nana, Petroula; Spanos, Konstantinos; Brotis, Alexandros; Fabre, Dominique; Mastracci, Tara; Haulon, Stephan
Abstract : Objective: Sarcopenia has been related to higher mortality rates after abdominal aortic aneurysm repair. This analysis aimed to assess sarcopenia related mortality and spinal cord ischaemia (SCI) at 30 days, and mortality during the available follow up, in patients with complex aortic aneurysms, managed with open or endovascular interventions. Data Sources: A search of the English literature, via Ovid, using Medline, EMBASE, and CENTRAL up to 15 June 2022 was done. Review Methods: This meta-analysis was conducted according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) guidelines and preregistered in PROSPERO (CRD42022338079). Observational studies (2000 – 2022), with five or more patients, reporting on sarcopenia related mortality and SCI at 30 days, and midterm mortality after thoraco-abdominal aneurysm repair (open or endovascular), were eligible. The ROBINS-I tool (Risk Of Bias In Non-Randomised Studies of Interventions) was used for risk of bias, and GRADE (Grading of Recommendations, Assessment, Development and Evaluation) for the assessment of evidence quality. The primary outcome was 30 day and midterm mortality, and the secondary outcome was SCI at 30 days, in sarcopenic and non-sarcopenic patients. The outcomes were summarised as odds ratio (OR) with 95% confidence intervals (CIs). Results: Four retrospective studies (1 092 patients; 40.0% sarcopenic) were included. Thirty day mortality was similar, with low certainty between groups (6% [95% CI 1 – 11] in sarcopenic vs. 5% [95% CI 1 – 9] non-sarcopenic patients [OR 0.30, 95% CI –0.21 – 0.81; p  = .94, Ι 2  = 0%). The estimated midterm mortality was statistically significantly higher (very low certainty) in sarcopenic patients (25% [95% CI 0.19 – 0.31] vs. 13% [95% CI –0.03 – 0.29] in non-sarcopenic patients (1.11 OR 0.95, 95% CI –0.21 – 2.44; p < .001, Ι 2  = 88.32%). SCI was significantly higher (very low certainty) in sarcopenic patients (19%, 95% CI 4 – 34) vs. 7% (95% CI 5 – 20) in non-sarcopenic patients (OR 1.80, 95% CI –0.17 – 3.78; Ι 2  = 82.4%), despite an equal distribution of aneurysm type between the groups. Conclusion: Early mortality does not appear to be affected by sarcopenia in patients treated for thoraco-abdominal aneurysms. However, sarcopenia may be associated with higher peri-operative SCI and midterm mortality rates.